Troubling humanity: towards a queer feminist critical psychology - Oliveira, J. M. (2014)
This text is based on an appraisal of theoretical developments in queer feminisms and seeks to translate such concerns to a field of inquiry that we call queer feminist critical psychology. The text uses the concept of homonormativity as a specific apparatus of heteronormativity to tackle sexual politics and neoliberalism and applied to two interrelated domains: citizenship and the family. Such a perspective entails a critique of these notions in terms of the exclusionary assumptions they are based on and read as an example of the effects of homonormativity. Issues of representability are also discussed within this framework showing how these family and citizenship concepts are only intelligible within the scope of certain assumptions of gender, sexuality and political economy. The article also analyses issues of recognition of humanity that are always already derived from these norms. The construction of alternative forms of knowledge, specifically queer feminist critical psychology, implies taking into account these intersected spheres to produce knowledge that is situated and attentive to these norms, for the purposes of deconstruction.